2009
DOI: 10.1038/ijo.2009.205
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin directly improves endothelial dysfunction in obese rats through the AMPK–eNOS Pathway

Abstract: Objective: Hypoadiponectinemia has been proved to be closely related to endothelial dysfunction in peripheral arteries and is thought to be an independent risk factor for cardiovascular disease. The objective of this study was to investigate whether adiponectin might independently improve endothelial dysfunction in aorta isolated from high-fat-diet-induced obese. SpragueDawley rat and to study the mechanism involved. Research Design and Subjects: Male Sprague-Dawley rats were fed with a regular or a high-fat d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
78
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(86 citation statements)
references
References 31 publications
6
78
1
1
Order By: Relevance
“…In contrast to our results, some studies (50,51) have shown a decrease in endothelium-dependent vasorelaxation and no alteration in the maximal contractile responses to PE in renal arteries from saturated and unsaturated fatty acid-fed rats, compared with control rats, but there was no marked difference between them (50). These authors used a 34.4% unsaturated fatty acid diet over a 24-week period, while our study used an 83% unsaturated fatty acid diet over a 19-week period.…”
Section: Vascular Reactivitycontrasting
confidence: 99%
“…In contrast to our results, some studies (50,51) have shown a decrease in endothelium-dependent vasorelaxation and no alteration in the maximal contractile responses to PE in renal arteries from saturated and unsaturated fatty acid-fed rats, compared with control rats, but there was no marked difference between them (50). These authors used a 34.4% unsaturated fatty acid diet over a 24-week period, while our study used an 83% unsaturated fatty acid diet over a 19-week period.…”
Section: Vascular Reactivitycontrasting
confidence: 99%
“…Ceolotto et al (41) reported that AMPK protects HUVEC against glucose-induced oxidative stress by suppressing hyperactivity of NAD(P)H oxidase. Deng et al (42) reported that AMPK protects human aortic endothelium by increasing NO production via endothelial NOS phosphorylation. In contrast to these studies, the present study revealed that AMPK protects the endothelium by inhibiting the dissociation between c-Abl and Prdx1.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, adiponectin also has a direct effect on the vascular system to exert vasodilator actions, and increased blood flow. Adiponectin increases NO production through two mechanisms, namely, by activation of endothelial nitric oxide synthase (eNOS) enzyme activity and via an increase in eNOS expression in endothelial cells 37,38) . Thus, decreased adiponectin levels cause vascular dysfunction in the presence of inflammatory and oxidative vascular injuries, and enhance the predisposition to renal dysfunction.…”
Section: Discussionmentioning
confidence: 99%